PENINGKATAN PENGUASAAAN MUFRADAT MAHASISWA MELALUI MEDIA BERBASIS TEKS CERITA - Nuur, Khaerun Nisa (Diwan: Jurnal Bahasa dan Sastra Arab, 2018)
This article discussed about the way of increasing the students' mastery of mufradat through the story of text media. The mastery process of mufradat is still less effective among them because they cannot use learning media well that caused the students are not interested in learning Arabic. Media has important roles in learning process. Media text stories are the story related to learning materials that serve to convey messages from lecturers to students. The way of using media as medium to increase mufradat mastery to improve the ability of Arabic students’ especially in mastery of mufradat and they can also improve their capability in mastering the appropriate method in learning process and selecting learning media effectively and efficiently.